Lower Urinary Pathogens: Do More Pathogenic Bacteria Increase the Risk of Pyelonephritis? - Rosett, Heather A.; Krischak, Madison K.; Sachdeva, Sarika; Weaver, Kristin E.; Heine, Robert Phillips; Denoble, Anna E.; Dotters-Katz, Sarah K. (American Journal of Perinatology, 2020)
Objective Outside of pregnancy, urinary pathogens such as Proteus and Klebsiella are considered more pathogenic than E. coli. During pregnancy, the implications of lower urinary tract infection (LUTI) with more pathogenic bacteria are unclear. Thus, we sought to compare the risk of progression from LUTI to pyelonephritis among women infected with these more pathogenic urinary bacteria to those infected with E. coli.Study Design Retrospective cohort of pregnant women with LUTI at single tertiary center from July 2013 to May 2019. Pathogenic infections (PI) were defined as asymptomatic bacteriuria or acute cystitis urinary cultures positive for Proteus, Klebsiella, Enterobacter, Citrobacter, Acinetobacter, Staphylococcus, or Raoultella species. Demographic, infectious, antepartum, and postpartum data abstracted. Pregnant women with PI compared with those with E. coli. Primary outcome was progression to pyelonephritis. Secondary outcomes included pyelonephritis length of stay (LOS) >6 days, preterm birth (PTB), low birthweight (LBW), and measures of pyelonephritis-related morbidity.Results Of 686 pregnant women with LUTIs, 313 had urine culture growing out either PI or E. coli, with 59 (12%) growing PI and 254 (54%) growing E. coli. Women with PI were more likely to be African American, have chronic hypertension, and have history of preeclampsia. The primary species causing PI were Klebsiella (n = 29) and Proteus (n = 11). PI were not more likely to progress to pyelonephritis than E. coli LUTIs (10.9 vs. 14.5%; p = 0.67). Median LOS for pyelonephritis and other measures of pyelonephritis-related morbidity did not differ nor did PTB or LBW rates. After controlling for race, body mass index, history of preeclampsia, and history of pyelonephritis, PI were not associated with increased odds of progression to pyelonephritis (adjusted odds ratio: 0.69, 95% confidence interval: 0.27–1.80).Conclusion Bacteria traditionally considered to be more pathogenic outside of pregnancy do not progress to pyelonephritis at higher rates than E. coli in pregnancy, and are associated with similar pyelonephritis-related morbidity. Larger studies are needed to confirm these findings.Key Points
Keywords: pregnancy; pyelonephritis; anemia; sepsis; urinary tract infection; uropathogens